Our Australian girl - Wang, Gabrielle (Penguin Books / Puffin, 2014)
It's 1941 ... and school is almost over - not just for summer, but forever. Darwin could be bombed any day, and everyone Pearlie knows is leaving for a safer place. Animals and pets of all kinds are being left behind, and Pearlie can't bear it. But can she rescue them all? And what will happen when it's her turn to leave the home she loves?Follow Pearlie on her adventure in the second of four exciting stories about a courageousgirl in a world at war